Summary report of Digestability and growth trial on Atlantic salmon in saltwater - Sutter, David; Traustason, Elvar Steinn; Lamborelle, Georges (Zenodo, 2022)
This report presents the results of a growth and digestibility trial performed by Matís for Laxá. Three feeds were analysed and evaluated with regard to their digestibility and their effect on the growth performance of Atlantic salmon (Salmo salar ) as well as the accumulation of fatty acids. The three commercial feeds were coated with yttrium and tested in triplicate tanks. Significant difference was found for the digestibility of crude proteinlysine, methionine, cystine, valine and threonine while no difference was found in the fatty acid composition and specific growth rates of fish fed from the three types of feed, indicating that the digestive qualities of the feeds meet the requirements of juvenile Atlantic salmon for optimal growth. Longer trials with bigger fish are recommended to determine if increased digestibility of crude protein and amino acids would result in difference in SGR% over a longer trial period. Funding: Laxá